2010
DOI: 10.1111/j.1525-1314.2010.00893.x
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphic history of a syn‐convergent orogen‐parallel detachment: The South Tibetan detachment system, Bhutan Himalaya

Abstract: The South Tibetan detachment system (STDS) in the Himalayan orogen is an example of normal-sense displacement on an orogen-parallel shear zone during lithospheric contraction. Here, in situ monazite U(-Th)-Pb geochronology is combined with metamorphic pressure and temperature estimates to constrain pressure-temperature-time (P-T-t) paths for both the hangingwall and footwall rocks of a Miocene ductile component of the STDS (outer STDS) now exposed in the eastern Himalaya. The outer STDS is located south of a y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
136
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(148 citation statements)
references
References 77 publications
(210 reference statements)
12
136
0
Order By: Relevance
“…Schärer, 1984), even if this should be rather minor (e.g. Kellett et al, 2010). As it can be seen from Fig.…”
Section: In-situ U-th-pb Geochronology and Age Interpretationsmentioning
confidence: 89%
“…Schärer, 1984), even if this should be rather minor (e.g. Kellett et al, 2010). As it can be seen from Fig.…”
Section: In-situ U-th-pb Geochronology and Age Interpretationsmentioning
confidence: 89%
“…Previous geochronologic studies have noted a correlation between monazite chemical zonation and U-Th-Pb age (e.g., Foster et al, 2002;Gibson et al, 2004;Kohn et al, 2005;Cottle et al, 2009a;Kellett et al, 2010). These studies have shown that individual grains are capable of recording evidence of multiple growth and resorption events and that the relative abundance of yttrium within the different zones can be linked to processes controlling the yttrium budget of the rock.…”
Section: Monazite Growth Resorption and Associated Implicationsmentioning
confidence: 97%
“…For a system subducting material of heterogeneous strength, the plunger model predicts episodic exhumation during the subduction of the stronger units. Based on geophysical evidence for a midcrustal ramp, this mechanism has been suggested for the exhumation of cryptic lower-crustal granulitized eclogites in Solid Earth, 4, 75-92, 2013 www.solid-earth.net/4/75/2013/ C. J. Warren: Exhumation of (ultra-)high-pressure terranes 85 the eastern Himalaya (Kellett et al, 2010;Grujic et al, 2011;Warren et al, 2011), but its operation may be difficult to prove in ancient collisional settings.…”
Section: Plunger Expulsionmentioning
confidence: 99%